Inorganic and stable isotope geochemistry of tropical Atlantic/Caribbean planktonic foraminifera : implications for the reconstruction of upper ocean temperatures and stratification - Regenberg, Marcus (2006)
Planktonic foraminifera from tropical Atlantic and Caribbean sediment-surface samples (0-1 cm) show general westward-directed increasing calcification depths depending on the east-west increase in thermocline depth. Positively related planktonic foraminiferal Mg/Ca and carbonate ion concentration in the Caribbean show well preserved Mg/Ca down to depths about 1.5 km above the lysocline, which equals a carbonate ion concentration of 26-18 µmol/kg. Species-specific calibrations of Mg/Ca with d18O-derived calcification temperatures reveal similar exponential and differing preexponential constants for shallow- and thermocline-dwelling compared to deep-dwelling species. For multispecies, a "warm water" and a "cold water" calibration was derived. Alteration of deep-sea sediments in the vicinity of the Bahama platform results in micro-scale inorganic crystallites on planktonic foraminiferal tests, which synchronize the absence of high Mg-calcite from the sediments. Mg/Ca and Sr/Ca of the crystallites are 4-6 times elevated and 2-3 times depleted, respectively, compared to the original foraminiferal test.